Prediction and identification of mouse cytotoxic T lymphocyte epitopes in Ebola virus glycoproteins - Wu Shipo; Yu Ting; Song Xiaohong; Yi Shaoqiong; Hou Lihua; Chen Wei (Virology Journal, 2012)
Abstract Background Ebola viruses (EBOVs) cause severe hemorrhagic fever with a high mortality rate. At present, there are no licensed vaccines or efficient therapies to combat EBOV infection. Previous studies have shown that both humoral and cellular immune responses are crucial for controlling Ebola infection. CD8+ T cells play an important role in mediating vaccine-induced protective immunity. The objective of this study was to identify H-2d-specific T cell epitopes in EBOV glycoproteins (GPs). Results Computer-assisted algorithms were used to predict H-2d-specific T cell epitopes in two species of EBOV (Sudan and Zaire) GP. The predicted peptides were synthesized and identified in BALB/c mice immunized with replication-deficient adenovirus vectors expressing the EBOV GP. Enzyme-linked immunospot assays and intracellular cytokine staining showed that the peptides RPHTPQFLF (Sudan EBOV), GPCAGDFAF and LYDRLASTV (Zaire EBOV) could stimulate splenoctyes in immunized mice to produce large amounts of interferon-gamma. Conclusion Three peptides within the GPs of two EBOV strains were identified as T cell epitopes. The identification of these epitopes should facilitate the evaluation of vaccines based on the Ebola virus glycoprotein in a BALB/c mouse model.